2021
DOI: 10.1007/s41810-021-00110-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Simple Bioaerosol Collection Filter System Using a Conventional Vacuum Cleaner for Sampling

Abstract: Although numerous bioaerosol samplers for counting and identifying airborne microorganisms are available, the considerably high purchase and maintenance costs for the sampler often prevent broad monitoring campaigns for occupational or environmental surveillance of bioaerosols. We present here a newly developed simple adapter and filter system (TOP filter system) designed to collect bioaerosol particles from a defined air volume using conventional vacuum cleaners as air pumps. We characterized the physical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Alternatively, others have similarly used a portable impactor with Petri dishes containing Vaseline [ 19 , 44 ], and filter cassettes with sampling pumps have also been used indoors [ 13 , 15 ]. Of note, a low-cost filter-based sampler operated with a conventional vacuum cleaner has been devised that may be used as an alternative to portable impactors with simple calibration [ 49 ]. The congruence between active devices in the estimation of fungal spore richness still requires investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, others have similarly used a portable impactor with Petri dishes containing Vaseline [ 19 , 44 ], and filter cassettes with sampling pumps have also been used indoors [ 13 , 15 ]. Of note, a low-cost filter-based sampler operated with a conventional vacuum cleaner has been devised that may be used as an alternative to portable impactors with simple calibration [ 49 ]. The congruence between active devices in the estimation of fungal spore richness still requires investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane filters, also potentially including microfluidic platforms, are often used for bioaerosol collection in highly contaminated environments[ 20 , 24 , 25 ]. The particles can be directly examined from the filter using an optical microscope or can be cultured by placing the filter on a culture medium.…”
Section: Aerosols Droplets and Collection/detection Methodsmentioning
confidence: 99%
“…However, metagenomic studies of air samples face some challenges regarding microbial density, standardized methodologies, and bioinformatics tools [208]. Fortunately, the advent of new technologies for sample collections (i.e., the TOP filter system), DNA sequencing (i.e., Illumina, PacBio, and Oxford Nanopore Technologies platforms), and analysis pipelines (i.e., MEGAN and QIIME2) have allowed for the application of air metagenomics to explore metabolic pathways, bioremediation methods, and biogeochemical cycles [20,209]. Although the low biomass feature of the air environment has resulted in a lower number of microbes than in soil and water media, metagenomic research has revealed differing abundances of microbial communities [210].…”
Section: Metagenomics In the Environmental Sciencesmentioning
confidence: 99%